Essential approximate point and essential defect spectrum of a sequence of linear operators in Banach spaces
This paper is devoted to an investigation of the relationship between the essential approximate point spectrum (respectively, the essential defect spectrum) of a sequence of closed linear operators (T_n)_nN on a Banach space X, and the essential approximate point spectrum (respectively, the essential defect spectrum) of a linear operator T on X, where (T_n)_nN converges to T, in the case of convergence in generalized sense as well as in the case of the convergence compactly, number=4, journal=Methods of Functional Analysis and Topology, author=Heraiz, T. and Ammar, A. and Jeribi, A., year=2019, month=Dec., pages=373–380